Long-term survival after surgical management of renal cell carcinoma with venous tumor thrombus - Mota, Yuliya Stepanivna (Journal of Education, Health and Sport, 2020)
The aim: to evaluate the long-term survival in patients after surgical management of renal cell carcinoma with venous tumor thrombus. Materials and methods. From 1993 to 2019 88 patients with renal cell carcinoma, complicated by venous tumor thrombus, were observed at the Vascular surgery department of Lviv Regional Clinical Hospital: 65 (73.9%) men, 23 (26.1%) women, mean age – 58.7 ± 1.9 years. Surgical management included radical nephrectomy in combination with thrombectomy from inferior vena cava and right atrium. Kaplan-Meier method and log-rank test were used for survival analysis. Results and discussion. Long-term survival was evaluated in 78 patients, the median follow-up was 51.6±14.3 months. Cumulative 2-, 5- and 10-year survival rates of patients with renal vein tumor thrombus (78.8%, 48.1%, 37.4%) were significantly higher compared to patients with intraatrial and inferior vena cava tumor thrombus (53.5%, 38.2%, 17.2%) (p<0.05). There was no significant difference in survival among patients with renal cell carcinoma, complicated with tumor venous thrombus, without and with metastases (p>0.05). Regarding to inferior vena cava tumor thrombus level there also was no significant difference in survival (p>0.05). As for the prognostic value of tumor histological gradation, the overall survival parameters were significantly higher in patients with G1-G2 compared with G3-G4 differentiation degrees of renal cell carcinoma (p<0.05). Conclusions. Radical nephrectomy with thrombectomy from inferior vena cava and right atrium remains the only curative treatment for patients with renal cell carcinoma and venous tumor thrombus that allows to provide reasonable long-term survival outcomes.